Endothelin-1/Endothelin Receptor Type A-Angiopoietins/Tie-2 Pathway in Regulating the Cross Talk Between Glomerular Endothelial Cells and Podocytes in Trichloroethylene-Induced Renal Immune Injury - Xie H; Wang H; Wu Q; Peng J; Huang H; Wang Y; Huang M; Jiang W; Yang Y; Zhang X; Zhang J; Zhu Q (Dove Medical Press, 2021)
Haibo Xie,1,2,* Hui Wang,1,2,* Qifeng Wu,3 Jiale Peng,4 Hua Huang,4 Yican Wang,4 Meng Huang,4 Wei Jiang,4 Yi Yang,4 Xuesong Zhang,4 Jiaxiang Zhang,2,4 Qixing Zhu1,2 1Department of Dermatology, First Affiliated Hospital of Anhui Medical University, Hefei, Anhui Province, People’s Republic of China; 2Key Laboratory of Dermatology (Anhui Medical University), Ministry of Education, Hefei, People’s Republic of China; 3Guangdong Province Hospital for Occupational Disease Prevention and Treatment, Guangzhou, Guangdong Province, People’s Republic of China; 4Department of Occupational Health and Environmental Health, School of Public Health, Anhui Medical University, Hefei, Anhui Province, People’s Republic of China*These authors contributed equally to this workCorrespondence: Jiaxiang ZhangDepartment of Occupational Health and Environmental Health, School of Public Health, Anhui Medical University, Hefei, Anhui, People’s Republic of ChinaTel +86-055163869267Email zhangjiaxiang@ahmu.edu.cnQixing ZhuDepartment of Dermatology, First Affiliated Hospital of Anhui Medical University, Hefei, Anhui, People’s Republic of ChinaEmail zqxing@yeah.netIntroduction: This study aimed to investigate the mechanism in regulating the cross talk between glomerular endothelial cells and podocytes in “occupational medicamentosa-like dermatitis induced by trichloroethylene (OMLDT)” patients.Methods: Totally 6 OMLDT patients, 18 controls, and 102 BALB/c female mice were involved in this study. Patient’s serum endothelin-1 (ET-1), angiopoietin-1 (Ang-1) and angiopoietin-2 (Ang-2), blood urea nitrogen (BUN), and podocalyxin (PCX) were detected. All the mice were used to establish the trichloroethylene (TCE) sensitized mouse model. Transmission electron microscope results were used to reflect renal glomerulus injury. Protein levels were detected by Western blot. Ang-1/Ang-2 gene level was reflected by RT-PCR. Cell apoptosis level was detected by using TUNEL assay kit.Results: We found that in OMLDT patients, ET-1, Ang-2, BUN, and PCX were highly expressed but Ang-1 was inhibited. In TCE sensitized positive mouse, the downregulation of Ang-1, pTie-2 and the upregulation of Ang-2 were mediated by ET-1/ETAR but not ET-1/ETBR. The promotor of apoptosis proteins was downregulated and the inhibitor of apoptosis proteins was upregulated by treating with BQ123.Discussion: ET-1/ETAR-Angs/Tie-2 pathway mediated the cross talk between glomerular endothelial cells and podocytes. BQ123 can alleviate glomerulus immune injury.Keywords: trichloroethylene, glomerular, endothelin-1, endothelin receptor type A, angiopoietin-1, angiopoietin-2